(untitled) (Asian Journal of Pharmaceutics (AJP), 2021)
Objective: A novel coronavirus disease (COVID-19) has spread all around the world. The progression from initial signs to a diagnosis of acute respiratory failure is usually related to spontaneous cytokine production. There is a growing need to classify appropriate medicines for treatment care. The inhibitory effect of chloroquine (CQ) is potential. However, CQ can lead to serious side effects. Various studies recommend hydroxychloroquine (HCQ) have similar antiviral effect as of CQ and maybe a better therapeutic solution. Therefore, we aim to explore the mechanism by which HCQ can inhibit replication of coronavirus. Materials and Methods: A retrospective study was carried out using online databases from 2003 to 2020. Results: The obtained results showed that HCQ can inhibit viral replication and entry inside the cell through raising lysosomal pH and binding to specific receptors on the cells, thereby, preventing viral entry. Conclusion: HCQ has a better safety profile than CQ and also modulates cytokine syndrome. However, further studies are needed to explore this mechanism.